Mesh sheet

JP7933528B2Active Publication Date: 2026-10-13MEIWA GURABIA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022073106
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-04-27
Publication Date
2026-10-13
Estimated Expiration
2042-04-27

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、衣服などに使用され、ポリエステルなどよりも融点の低いナイロンやウレタンなどの化学繊維と挟持して貼り合わせて一つの生地とするときに、ポリエステル繊維同士を貼り合わせるときの一般的な温度より低温で接着しても貼り合わせた生地が剥がれない実用上の強度を有することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933528000001
    Figure 0007933528000001
  • Figure 0007933528000002
    Figure 0007933528000002
Patent Text Reader

Abstract

To provide a mesh-like sheet that is mainly used in making garments and is held between chemical fibers such as nylon and urethane with lower melting points than those of polyester and the like and laminated on them, fabricating one material, wherein it can exhibit practically sufficient strength to prevent the peeling of laminated material even when bonded at lower temperatures than general temperatures for bonding polyester fibers.SOLUTION: A mesh-like sheet with multiple holes comprises a thermoplastic elastomer with copolymers of vinyl aromatic and conjugated diene compounds being partly hydrogenated, and a hydrocarbon-based softener, with a melt flow rate of 10-60 g / 10 min (190°C, 2.16 kgf).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a mesh-like sheet used for bonding together chemical fibers such as polyester, nylon, and urethane, which are used in clothing and the like. [Background technology]

[0002] Traditionally, mesh-like sheets have been used in various applications, such as clothing including innerwear, due to their rubbery elasticity, stretchability, and breathability.

[0003] For example, Patent Document 1 discloses a mesh-like sheet having an opening ratio of 5 to 50% obtained by melt-blown a resin composition containing 50 to 300 parts by mass of a hydrocarbon-based rubber softener per 100 parts by mass of a block copolymer obtained by hydrogenating a block copolymer consisting of a polymer block A mainly composed of at least two vinyl aromatic compounds, each having a weight-average molecular weight of 200,000 or less, and a polymer block B mainly composed of at least one conjugated diene compound. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2017-186719 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] However, while polyethylene terephthalate, a representative polyester, has a melting point of approximately 260°C, and polyester fibers are generally bonded together using a mesh sheet, the melting point of nylon 6, a type of nylon, is approximately 230°C, and the melting point of polyurethane varies depending on the type but is between 150°C and 230°C. Therefore, when bonding chemical fibers such as nylon or urethane, which have lower melting points than polyester, if the mesh sheet described in Patent Document 1 is bonded together with nylon or urethane and heated, there is a problem that the chemical fibers with lower melting points, such as nylon or urethane, may begin to melt and be damaged before the mesh sheet melts.

[0006] Therefore, the present invention aims to provide a mesh-like sheet that has practical strength so that the bonded fabric does not peel off even when bonded at a lower temperature than the typical temperature for bonding polyester fibers together, when used in clothing and other applications and bonded together with chemical fibers such as nylon or urethane, which have a lower melting point than polyester, to form a single fabric. [Means for solving the problem]

[0007] [1] That is, the present invention relates to a thermoplastic elastomer having a Shore A hardness of 30 to 100 at 23°C, in which a portion of the double bonds derived from butadiene or isoprene of a copolymer using styrene as a vinyl aromatic and butadiene or isoprene as a conjugated diene is hydrogenated, and a hydrocarbon softener Composed of The mesh-like sheet is characterized by having a weight ratio of (thermoplastic elastomer) / (hydrocarbon-based softener) = 75 / 25~60 / 40, a melt flow rate of 10~60 g / 10 min (190°C, 2.16 kgf), and having multiple pores.

[0008] [2] The mesh-like sheet described in [1] above, characterized in that its melt viscosity at 150°C is 1000 to 3500 Pa·s.

[0009] [3] The mesh sheet according to [1] or [2] above, characterized in that the tensile permanent set is 10% or less.

[0011] [5] The mesh sheet according to [1] or [2], characterized in that the porosity due to the holes is 10 to 70%. [Effects of the Invention]

[0012] According to the present invention, when used in clothing and other applications, and when bonding polyester fibers with other chemical fibers such as nylon or urethane, which have a lower melting point than polyester, to form a single fabric, the bonded fabric can have practical strength that prevents peeling even when bonded at a lower temperature than the typical temperature for bonding polyester fibers together. [Modes for carrying out the invention]

[0013] The embodiments relating to the mesh-like sheet of the present invention will be described in detail below. In the description, the notation "~" indicating a range includes both an upper and lower limit.

[0014] The thermoplastic elastomer in the present invention is a polymer compound obtained by partially hydrogenating a copolymer of a vinyl aromatic and a conjugated diene compound, and has the property of behaving as a rubber or a plastic depending on the usage environment. In terms of physical properties such as elasticity, it has an intermediate value between rubber and plastic at a normal temperature of 20 to 30°C, so it has plastic-like hardness as well as rubber-like flexibility and stretchability. Further, in the thermoplastic elastomer, in the above-mentioned copolymer of the vinyl aromatic and the conjugated diene compound, hydrogen molecules are partially added, so that part of the double bonds derived from the conjugated diene become single bonds. As described above, in the copolymer of the vinyl aromatic and the conjugated diene compound, by hydrogenating a part of the double bonds derived from the conjugated diene, compared with full hydrogenation, the thermoplastic elastomer can maintain a predetermined strength, and is easily melted at a low temperature with improved viscoelasticity. As a specific example of the thermoplastic elastomer, for example, when styrene is used as the vinyl aromatic and butadiene is used as the conjugated diene, in the copolymer of styrene and butylene·ethylene (when butadiene is 1,4-bonded, it has a butylene skeleton, and when it is 1,2-bonded, it has an ethylene skeleton), a plurality of butylene moieties and ethylene moieties are partially hydrogenated to form butane moieties and ethane moieties. In addition, as for the thermoplastic elastomer, only one type may be used, or two or more types may be used in combination.

[0015] In the thermoplastic elastomer of the present invention, in the precursor copolymer, examples of the vinyl aromatic include styrene, and examples of the conjugated diene include butadiene and isopre Nna ne are used. The weight ratio of the vinyl aromatic to the conjugated diene is preferably (vinyl aromatic) / (conjugated diene) = 10 / 90 to 40 / 60, and more preferably 15 / 85 to 35 / 65. When the weight ratio of the vinyl aromatic to the conjugated diene is within the above range, the melting temperature of the mesh sheet of the present invention can be lowered, and sufficient adhesive strength can be achieved without damaging the chemical fibers even when the mesh sheet is sandwiched between and bonded to chemical fibers having a low melting point.

[0016] Further, in the thermoplastic elastomer of the present invention, the melt flow rate is preferably 0 to 50 g / 10 min under a load of 5 kgf at 230°C, more preferably 0 to 30 g / 10 min. When the melt flow rate is within the above range, the mesh sheet of the present invention can have a low melting temperature, and even when sandwiched between and bonded to chemical fibers with a low melting point, it can exhibit sufficient adhesive strength without damaging the chemical fibers. The melt flow rate is measured in accordance with standards such as JIS K7210-1.

[0017] Further, in the thermoplastic elastomer of the present invention, the specific gravity is preferably 0.86 to 0.93, more preferably 0.89 to 0.91. When the specific gravity is within the above range, the mesh sheet of the present invention can have a low melting temperature, and even when sandwiched between and bonded to chemical fibers with a low melting point, it can exhibit sufficient adhesive strength without damaging the chemical fibers.

[0018] Further, in the thermoplastic elastomer of the present invention, the durometer type A (Shore A) hardness measured according to JIS K6253-3:2012 at 23°C is preferably 30 to 100, more preferably 50 to 80. hardness When the above parameter is within the above range, the mesh sheet of the present invention can have a low melting temperature, and even when sandwiched between and bonded to chemical fibers with a low melting point, it can exhibit sufficient adhesive strength without damaging the chemical fibers.

[0019] The content ratio of the thermoplastic elastomer in the mesh sheet of the present invention is preferably 60 to 75 wt%, more preferably 64 to 70 wt%. When the content ratio of the thermoplastic elastomer is within the above range, the mesh sheet of the present invention can have a low melting temperature, and even when sandwiched between and bonded to chemical fibers with a low melting point, it can exhibit sufficient adhesive strength without damaging the chemical fibers.

[0020] The hydrocarbon-based softener in this invention is a compound containing hydrocarbon components that softens a mesh-like sheet compared to when no additive is used. Specifically, hydrocarbon-based softeners include compounds containing a large amount of liquid chain hydrocarbons (paraffinic oils), compounds containing a large amount of liquid cyclic hydrocarbons (naphthenic oils), and so on.

[0021] The kinematic viscosity of hydrocarbon-based softeners is 30-450 mm² at 40°C. 2 It is preferable that the value be / s, and the range is 60-410 mm. 2 It is even more preferable that the kinematic viscosity of the hydrocarbon softener is within the above range. When the kinematic viscosity of the mesh sheet of the present invention is within the above range, the melting temperature can be lowered, and sufficient adhesive strength can be obtained without damaging the chemical fibers even when the sheet is sandwiched and bonded to chemical fibers with low melting points. The kinematic viscosity is measured in accordance with standards such as JIS K2283.

[0022] The hydrocarbon-based softener content in the mesh-like sheet of the present invention is preferably 25 to 40% by weight, and more preferably 30 to 36% by weight. When the hydrocarbon-based softener content is within the above range, the melting temperature of the mesh-like sheet of the present invention can be lowered, and sufficient adhesive strength can be achieved without damaging the chemical fibers even when the sheet is sandwiched and bonded to chemical fibers with low melting points.

[0023] The mesh-like sheet of the present invention is preferably composed of the thermoplastic elastomer described above and the hydrocarbon-based softener described above. For example, if other components such as tackifiers are included, the melting temperature cannot be lowered when the mesh-like sheet is formed, which may cause damage to the chemical fibers when the sheet is sandwiched and bonded together with chemical fibers that have a low melting point.

[0024] Furthermore, in the mesh-like sheet of the present invention, the melt flow rate is preferably 10 to 60 g / 10 min, and more preferably 13 to 50 g / 10 min, when a load of 2.16 kgf is applied at 190°C. When the melt flow rate is within the above range, the melting temperature of the mesh-like sheet of the present invention can be lowered, and sufficient adhesive strength can be achieved without damaging the chemical fibers even when sandwiched and bonded together with chemical fibers that have a low melting point. Moreover, the melt flow rate is preferably 1 to 10 g / 10 min, when a load of 2.16 kgf is applied at 150°C, more preferably 2 to 15 g / 10 min, when a load of 2.16 kgf is applied at 160°C, more preferably 3 to 25 g / 10 min, when a load of 2.16 kgf is applied at 170°C, and more preferably 5 to 30 g / 10 min, when a load of 2.16 kgf is applied at 180°C. The melt flow rate is measured in accordance with standards such as JIS K7210-1.

[0025] Furthermore, the mesh-like sheet of the present invention preferably has a melt viscosity at 150°C of 1000 to 3500 Pa·s, and more preferably 1400 to 3300 Pa·s. When the melt viscosity of the mesh-like sheet at 150°C is within the above range, it can melt even at a relatively low temperature such as 140 to 150°C when sandwiched and bonded to chemical fibers with low melting points, and the chemical fibers can be bonded together with sufficient strength for use. Moreover, the melt viscosity is preferably 500 to 2000 Pa·s at 170°C, and preferably 300 to 1000 Pa·s at 190°C. The melt viscosity is measured in accordance with standards such as JIS K7199.

[0026] Furthermore, in the mesh-like sheet of the present invention, the weight ratio of thermoplastic elastomer to hydrocarbon-based softener is preferably thermoplastic elastomer / hydrocarbon-based softener = 75 / 25 to 60 / 40, and more preferably 70 / 30 to 64 / 36. When the weight ratio of thermoplastic elastomer to hydrocarbon-based softener is within the above range, the melting temperature of the mesh-like sheet of the present invention can be lowered, and sufficient adhesive strength can be achieved without damaging chemical fibers even when sandwiched and bonded together.

[0027] Furthermore, the mesh-like sheet of the present invention preferably has a tensile permanent set of 10% or less, and more preferably 1.0 to 7.0%. When the tensile permanent set of the mesh-like sheet is within the above range, when it is sandwiched and bonded with low-melting-point chemical fibers to form a fabric such as clothing, it is less likely to become wrinkled or saggy even if the fabric stretches during wear, and can be worn repeatedly. The tensile permanent set is measured in accordance with standards such as JIS K6273.

[0028] Furthermore, the mesh-like sheet of the present invention preferably has a porosity of 10 to 70%, and more preferably 20 to 60%. When the porosity of the mesh-like sheet is within the above range, when it is sandwiched and bonded to low-melting-point chemical fibers to form a fabric such as clothing, breathability can be ensured when worn, and sufficient adhesive strength can be achieved without damaging the chemical fibers. Note that the porosity is 10 cm 2 The ratio of the total area of ​​holes in the mesh-like sheet can be determined by methods such as image processing.

[0029] Furthermore, the mesh-like sheet of the present invention has a basis weight of 30 to 300 g / m². 2 Preferably, it is 50-200 g / m 2It is even more preferable that the basis weight of the mesh sheet is within the above range. When it is sandwiched between low-melting-point chemical fibers and bonded to form a fabric such as clothing, the weight will not become too heavy, and sufficient adhesive strength can be achieved without damaging the chemical fibers. [Examples]

[0030] [Example 1] As a thermoplastic elastomer, 50 parts by weight of styrene-ethylene-butylene copolymer a-1 (specific gravity 0.89, melt flow rate 11 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 65) in which a portion of the double bonds derived from the butadiene of the styrene-butadiene copolymer is hydrogenated; 20 parts by weight of styrene-ethylene-butylene copolymer a-5 (specific gravity 0.91, melt flow rate 2.5 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 70) in which a portion of the double bonds derived from the butadiene of the styrene-butadiene copolymer is hydrogenated; and as a hydrocarbon softener, liquid paraffin b-1 (kinematic viscosity at 40°C: 90.5 mm²) 2 A composition of 100 parts by weight was prepared using 30 parts by weight of ( / sec), melted and mixed while varying the temperature at 120-220°C, and then compressed and molded in a predetermined mold. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 30%.

[0031] [Example 2] As thermoplastic elastomers, 30 parts by weight of styrene-ethylene / butylene copolymer a-1 (specific gravity: 0.89, melt flow rate under a load of 5 kgf at 230°C: 11 g / 10 min, hardness (Shore A): 65), which is a copolymer of styrene and butadiene with some of the butadiene-derived double bonds hydrogenated, 30 parts by weight of styrene-ethylene / butylene copolymer a-2 (specific gravity: 0.91, melt flow rate under a load of 5 kgf at 230°C: 5.0 g / 10 min, hardness (Shore A): 75), which is a copolymer of styrene and butadiene with some of the butadiene-derived double bonds hydrogenated, and 10 parts by weight of styrene-ethylene / butylene copolymer a-5 (specific gravity: 0.91, melt flow rate under a load of 5 kgf at 230°C: 2.5 g / 10 min, hardness (Shore A): 70), which is a copolymer of styrene and butadiene with some of the butadiene-derived double bonds hydrogenated, and as a hydrocarbon-based softener, liquid paraffin b-1 (kinematic viscosity at 40°C: 90.5 mm 2 / sec) in an amount of 30 parts by weight were blended to prepare 100 parts by weight of a composition, which was melt-kneaded while varying the temperature in the range of 120 to 220°C, and then compression-molded using a predetermined mold. The produced mesh-like sheet had a basis weight of 100 g / m 2 , and a porosity due to a plurality of pores of 30%.

[0032] [Example 3] As thermoplastic elastomers, 45 parts by weight of styrene-ethylene / butylene copolymer a-1 (specific gravity: 0.89, melt flow rate under a load of 5 kgf at 230°C: 11 g / 10 min, hardness (Shore A): 65), which is a copolymer of styrene and butadiene with some of the butadiene-derived double bonds hydrogenated, 20 parts by weight of styrene-ethylene / butylene copolymer a-5 (specific gravity: 0.91, melt flow rate under a load of 5 kgf at 230°C: 2.5 g / 10 min, hardness (Shore A): 70), which is a copolymer of styrene and butadiene with some of the butadiene-derived double bonds hydrogenated, and as a hydrocarbon-based softener, liquid paraffin b-1 (kinematic viscosity at 40°C: 90.5 mm 2A composition was prepared using 35 parts by weight of ( / sec) to make 100 parts by weight. This was melted and mixed while varying the temperature between 120 and 220°C, and then compressed and molded in a predetermined mold. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 30%.

[0033] [Example 4] As thermoplastic elastomers, 20 parts by weight of styrene-ethylene-butylene copolymer a-1 (specific gravity 0.89, melt flow rate of 11 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 65) in which a portion of the double bonds derived from the butadiene of the styrene-butadiene copolymer is hydrogenated, and styrene-ethylene-butylene copolymer a-4 (specific gravity 0.89, at 230°C under a load of 5 kgf) 20 parts by weight of a styrene-ethylene-butylene copolymer a-6 (specific gravity 0.91, melt flow rate 2.4 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 50), 24 parts by weight of a styrene-ethylene-butylene copolymer a-6 (specific gravity 0.91, melt flow rate 2.4 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 76), and a hydrocarbon softener, liquid paraffin b-1 (kinematic viscosity at 40°C: 90.5 mm²). 2 A composition was prepared using 36 parts by weight of ( / sec) to make 100 parts by weight. This was melted and mixed while varying the temperature between 120 and 220°C, and then compressed and molded in a predetermined mold. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 30%.

[0034] [Example 5] Except for the mold used to produce the mesh-like sheet, the materials and methods were the same as in Example 1. The resulting mesh-like sheet had a basis weight of 50 g / m². 2 The porosity due to multiple pores was 30%.

[0035] [Example 6] Except for the mold used to produce the mesh-like sheet, the materials and methods were the same as in Example 1. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 50%.

[0036] [Example 7] Except for the mold used to produce the mesh-like sheet, the materials and methods were the same as in Example 1. The resulting mesh-like sheet had a basis weight of 150 g / m². 2 The porosity due to multiple pores was 50%.

[0037] [Example 8] Except for the mold used to produce the mesh-like sheet, the materials and methods were the same as in Example 1. The resulting mesh-like sheet had a basis weight of 200 g / m². 2 The porosity due to multiple pores was 30%.

[0038] [Comparative Example 1] As thermoplastic elastomers, 35 parts by weight of styrene-ethylene-butylene copolymer a-1 (specific gravity 0.89, melt flow rate 11 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 65) in which a portion of the double bonds derived from the butadiene of the styrene-butadiene copolymer is hydrogenated, and 35 parts by weight of styrene-ethylene-butylene copolymer a-2 (specific gravity 0.91, 230 35 parts by weight of a styrene-ethylene-butylene copolymer a-3 (specific gravity 0.91, melt flow rate 0 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 75) in which some of the double bonds derived from the butadiene of the styrene-butadiene copolymer are hydrogenated; and liquid paraffin b-1 (kinematic viscosity at 40°C: 90.5 mm) as a hydrocarbon softener. 2A composition of 100 parts by weight was prepared using 24 parts by weight of ( / sec), melted and mixed while varying the temperature at 120-220°C, and then compressed and molded in a predetermined mold. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 30%.

[0039] [Comparative Example 2] As a thermoplastic elastomer, 60 parts by weight of styrene-ethylene-butylene copolymer a-2 (specific gravity 0.91, melt flow rate 5.0 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 75) in which a portion of the double bonds derived from the butadiene of the styrene-butadiene copolymer is hydrogenated; 10 parts by weight of styrene-ethylene-butylene copolymer a-5 (specific gravity 0.91, melt flow rate 2.5 g / 10 min at 230°C under a load of 5 kgf, hardness (Shore A) 70) in which a portion of the double bonds derived from the butadiene of the styrene-butadiene copolymer is hydrogenated; and as a hydrocarbon softener, liquid paraffin b-1 (kinematic viscosity at 40°C: 90.5 mm²) 2 A composition of 100 parts by weight was prepared using 30 parts by weight of ( / sec), melted and mixed while varying the temperature at 120-220°C, and then compressed and molded in a predetermined mold. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 30%.

[0040] [Comparative Example 3] Except for the mold used to produce the mesh-like sheet, the materials and methods were the same as those used in Comparative Example 1. The resulting mesh-like sheet had a basis weight of 100 g / m². 2 The porosity due to multiple pores was 50%.

[0041] [Comparative Example 4] Except for the mold used to produce the mesh-like sheet, the materials and methods were the same as those used in Comparative Example 2. The resulting mesh-like sheet had a basis weight of 50 g / m². 2 The porosity due to multiple pores was 80%.

[0042] Table 1 shows the composition of each thermoplastic elastomer and hydrocarbon softener, the melt flow rate (MFR) (g / 10 min) at 2.16 kgf at 150°C, 160°C, 170°C, 180°C, and 190°C, the melt viscosity (Pa·S) at 150°C, 170°C, and 190°C, the basis weight, and the porosity for each example. The melt flow rate was measured in accordance with JIS K7210-1, and the melt viscosity was measured in accordance with JIS K7199.

[0043] [Table 1]

[0044] As described above, the modulus, breaking strength, and tensile permanent strain of each mesh-like sheet were measured. The peel strength when each mesh-like sheet was heated and bonded was also measured.

[0045] [Modulus] In accordance with JIS K7161-1, a tensile testing machine (Shimadzu Corporation, model AGS-1kNX) was used to measure the stress required to return each 15cm x 5cm mesh sheet to its original shape after 100% elongation. The stress was measured five times in both the direction of flow (MD) and the direction perpendicular to it (TD) at a tensile speed of 100mm / min in a 23°C atmosphere with a gripping distance of 10cm, and the arithmetic mean was calculated. A stress of 3N / 50mm or less was considered desirable because it indicates good conformability when bonded with synthetic fibers to form a fabric, while a stress greater than 3N / 50mm was considered undesirable.

[0046] [Breaking strength] In accordance with JIS K7161-1, a tensile testing machine (Shimadzu Corporation, model AGS-1kNX) was used to test each 15cm x 5cm mesh sheet. The stress at fracture was measured five times in both the direction of flow (MD) and the direction perpendicular to it (TD) of the mesh sheet at a tensile speed of 100mm / min in a 23°C atmosphere with a gripping distance of 10cm, and the arithmetic mean was calculated. A stress of 16N / 50mm or less was considered desirable because it would allow for good stretching when bonded with synthetic fibers to form a fabric, while a stress greater than 16N / 50mm was considered undesirable.

[0047] [Tensile permanent strain] In accordance with JIS K6273, a tensile testing machine (Shimadzu Corporation, model AGS-1kNX) was used to test 15cm x 5cm mesh sheets. Each sheet was stretched to 100% and left standing for 10 minutes at a tensile speed of 100mm / min in a 23°C atmosphere, and then allowed to shrink freely for another 10 minutes. The tensile set was calculated as a percentage using the formula {(length after shrinkage) - (length before stretching) / (length before stretching)} × 100. Each sheet was measured five times, and the arithmetic mean was calculated. If there is no difference between the length after shrinkage and the length before stretching, the tensile set is 0%. A set of 10% or less is considered desirable because it is less likely to become wrinkled or saggy when the fabric is laminated with synthetic fibers and worn. A set of 10% or more is considered undesirable.

[0048] [Peel strength] First, each mesh sheet is made of two 100% polyester sheets (made by debs, product name DS-0003, basis weight 80g / m²). 2The mesh-like sheets were clamped together and heated at either 140°C or 150°C to bond them into a single sheet. Then, in accordance with JIS L1086:2013, the peel strength was calculated using a tensile testing machine (Shimadzu Corporation, model AGS-1kNX). A peel strength of 30 N / 25 mm or higher was considered desirable, indicating that the chemical fibers were firmly bonded, while a value of less than 30 N / 2550 mm was considered undesirable. Furthermore, during peeling, it was confirmed whether the failure was cohesive failure of the mesh-like sheet or interfacial failure between the mesh-like sheet and the chemical fibers, and cohesive failure of the mesh-like sheet was judged to indicate a more desirable bond.

[0049] Regarding these evaluation results, tensile permanent strain and peel strength, which particularly affect the quality when the mesh-like sheet is actually sandwiched between chemical fibers to produce the fabric, were judged as good if both were favorable examples, and as poor if either one was an unfavorable example.

[0050] The results for modulus, breaking strength, tensile permanent strain, and peel strength for Examples 1-8 and Comparative Examples 1-4 are shown in Table 2, respectively.

[0051] [Table 2]

[0052] As shown in Table 2, a mesh-like sheet consisting of a styrene-ethylene-butylene copolymer in which some of the double bonds derived from the butadiene of a predetermined styrene-butadiene copolymer are hydrogenated, and a predetermined liquid paraffin, and having a predetermined melt flow rate, was found to have excellent conformability and elongation in modulus, breaking strength, and tensile permanent strain, and was less prone to becoming flimsy even when stretched. It was also found to melt and adhere firmly even when bonded to a fabric at temperatures of 140°C or 150°C, which are generally lower than when using polyester fibers.

Claims

1. A thermoplastic elastomer having a Shore A hardness of 30 to 100 at 23°C, in which a portion of the double bonds derived from butadiene or isoprene in a copolymer using styrene as a vinyl aromatic and butadiene or isoprene as a conjugated diene is hydrogenated, Composed of hydrocarbon-based softeners, The weight ratio of the thermoplastic elastomer to the hydrocarbon-based softener is (thermoplastic elastomer) / (hydrocarbon-based softener) = 75 / 25 to 60 / 40. The melt flow rate is 10-60 g / 10 min (190°C, 2.16 kgf), A mesh-like sheet characterized by having multiple holes.

2. The mesh-like sheet according to claim 1, characterized in that its melt viscosity at 150°C is 1,000 to 3,500 Pa·s.

3. The mesh-like sheet according to claim 1 or 2, characterized in that the tensile permanent set is 10% or less.

4. The mesh-like sheet according to claim 1 or 2, characterized in that the porosity due to the holes is 10 to 70%.

Citation Information

Patent Citations

  • Air permeable pressure-sensitive adhesive sheet

    JP1995109443A

  • Hot-melt adhesive composition

    JP1996060121A

  • Hot melt composition for toilet seat sheet and toilet seat sheet

    JP2008248115A

  • Hydrogenated block copolymer

    JP2017149954A

  • Mesh-like sheet

    JP2017186535A